Bismuth-based titanium-based heterojunction, preparation method thereof and application of bismuth-based titanium-based heterojunction in degradation of benzene-containing wastewater

Through the preparation of titanium -based Z -type heterogeneous knot materials, the problem of low efficiency of traditional photocatalysts when dealing with antioxidant dye wastewater, and achieve efficient photocatalytic degradation effects, especially in terms of degradation of benzene -containing wastewater. A significant degradation rate.

CN119368157APending Publication Date: 2025-01-28YANGZHOU POLYTECHNIC INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411579837.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Traditional biological methods are difficult to effectively treat dye wastewater with oxidation resistance and light stability, and existing photocatalysts have problems such as slow charge carrier migration, low recombination efficiency and insufficient visible light absorption.

Method used

The titanium -based Z -type heterogeneous knot material is used to synthesize the composite heterogeneous knot of chlorine oxide, titanium dioxide, graphite nitride, and NIFE2O4 through the water heat self -assembly method, and distribute the surface active molecules on its surface to guide the growth of thermal insulation , Improve optical catalytic performance.

Benefits of technology

It significantly improves the optical reduction capacity and charge separation efficiency, and improves the treatment effect of photocatalytic wastewater, especially in terms of degradation of benzene -containing wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a bismuth-based titanium-based heterojunction, a preparation method of the bismuth-based titanium-based heterojunction and application of the bismuth-based titanium-based heterojunction in degradation of benzene-containing wastewater. Comprising a bismuth-based titanium-based heterojunction and surface active molecules, the bismuth-based titanium-based heterojunction comprises bismuth oxychloride, titanium dioxide, graphite-phase carbon nitride and NiFe2O4, and the bismuth-based titanium-based heterojunction material is prepared by distributing the surface active molecules on the bismuth-based titanium-based heterojunction and guiding thermal-insulation growth. The bismuth-based titanium-based heterojunction material is a Z-type heterojunction composite material, and is applied to treatment of dye pollutants in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heterojunction materials, and more specifically, to a bismuth-based titanium-based heterojunction, a preparation method thereof, and an application thereof in degrading benzene-containing wastewater. Background Art

[0002] With the expansion of production scale and the improvement of industrialization, the output of difficult-to-degrade industrial wastewater such as dye wastewater is increasing. Dyes are widely used in papermaking, textiles, printing and other fields. How to efficiently and thoroughly treat dye wastewater is one of the key issues that must be considered to achieve ecological harmony. Dyes usually have a special aromatic structure, which leads to strong antioxidant and light stability of dye wastewater. It is difficult to guarantee the effect of traditional biological methods when treating such wastewater. In recent years, advanced oxidation processes (AOPs) based on photocatalysts have attracted widespread attention as a promising new frontier for environmentally friendly and sustainable wastewater treatment technology. The efficient use of photocatalytic technology is of great significance for a clean environment. Bismuth-based photocatalysts are a type of visible light-responsive wastewater treatment photocatalyst due to their non-toxicity, low cost, modifiable morphology, and excellent optical and chemical properties. In the research progress of bismuth-based photocatalysts for wastewater treatment, bismuth-based photocatalysts have limitations on original photocatalysts, such as slow migration of charge carriers, charge carrier recombination, and low visible light absorption.

[0003] In practical applications, bismuth-based titanium-based heterojunction materials can be used to degrade organic pollutants in aqueous solutions, including benzene compounds. By constructing a BiOCl / bismuth-based halide perovskite heterojunction, the photoredox ability and charge separation efficiency can be effectively improved, thereby improving the photocatalytic wastewater treatment effect. In addition, the bismuth titanate / carbon nitride inorganic-organic composite S-type heterojunction also demonstrated the ability to artificially photosynthesize hydrogen peroxide in a pure water environment, which shows the great potential of bismuth-based heterojunction materials in environmental governance. Summary of the invention

[0004] The invention provides a bismuth-based titanium-based heterojunction and application thereof in degrading benzene-containing wastewater. The bismuth-based titanium-based heterojunction material is a composite material having a Z-type heterojunction and is applied to treating dye pollutants in water.

[0005] In the first aspect, the present invention provides a bismuth-titanium-based heterojunction material, including a bismuth-titanium-based heterojunction and a surfactant molecule. The bismuth-titanium-based heterojunction includes bismuth oxychloride, titanium dioxide, graphite phase carbon nitride and NiFe2O4. The bismuth-titanium-based heterojunction material is obtained by distributing the surfactant molecules on the bismuth-titanium-based heterojunction and guiding the thermal insulation growth.

[0006] Preferably, the bismuth oxychloride, titanium dioxide, graphite carbon nitride and NiFe2O4 are used to synthesize a heterojunction by a hydrothermal self-assembly method.

[0007] In a second aspect, the present invention provides a method for preparing a bismuth-based titanium-based heterojunction material, comprising the following steps: (1) Bismuth-based titanium heterojunction was prepared by hydrothermal self-assembly of bismuth oxychloride, titanium dioxide, graphite carbon nitride and NiFe2O4; (2) The surfactant molecules are distributed on the bismuth-titanium-based heterojunction, and the bismuth-titanium-based heterojunction material is prepared by a hydrothermal method, in which the surfactant molecules guide the heat preservation growth.

[0008] Preferably, in step (1), the mass ratio of bismuth oxychloride, titanium dioxide, graphite carbon nitride and NiFe2O4 is 20-100:5-12:3-5:8-11.

[0009] Preferably, in step (1), the mass ratio of bismuth oxychloride, titanium dioxide, graphite carbon nitride and NiFe2O4 is 50-100:8-12:3-5:8-10.

[0010] Preferably, in step (1), the mass ratio of bismuth oxychloride, titanium dioxide, graphite carbon nitride and NiFe2O4 is 100:12:5:11.

[0011] Preferably, in step (1), the particle size of bismuth oxychloride is 50 to 300 nm.

[0012] Preferably, in step (1), the particle size of bismuth oxychloride is 50 to 200 nm.

[0013] Preferably, in step (1), the particle size of bismuth oxychloride is 180 nm.

[0014] Preferably, in step (1), the particle size of the bismuth-based titanium-based heterojunction is 300 to 600 nm.

[0015] Preferably, in step (1), the particle size of the bismuth-based titanium-based heterojunction is 400-500 nm.

[0016] Preferably, in step (1), the particle size of the bismuth-based titanium-based heterojunction is 500 nm.

[0017] Preferably, in step (2), the hydrothermal reaction is carried out at 170-200° C. for 14-16 hours.

[0018] Preferably, in step (2), the surfactant molecule is a fatty amine, the temperature of the thermal insulation growth is 60-80° C., and the thermal insulation growth time is 100-120 min.

[0019] In a third aspect, the present invention provides an application of a bismuth-based titanium-based heterojunction material in treating pollutants.

[0020] In a fourth aspect, the present invention provides an application of a bismuth-based titanium-based heterojunction material in degrading benzene-containing wastewater.

[0021] In summary, the present invention has the following beneficial effects: 1. The photocatalytic performance of the Z-type heterojunction material based on TiO2 in the present invention for degrading dyes. TiO2 generally acts as an electron donor in the Z-type heterostructure because of its very positive valence band position and greater hole potential; the special electron migration path of the Z-type heterojunction retains the high-potential photogenerated holes generated on TiO2, improves the oxidation capacity of the catalytic system, and consumes the photogenerated electrons with relatively low potential, effectively inhibiting the carrier recombination in the TiO2 phase. In addition, the introduction of precious metals will also cause the composite material to transform from a pn junction to a Z-type heterojunction. The activity of the photocatalyst is affected by the size of the semiconductor particles. The particles in nanostructures such as nanorods and nanotubes have higher activity and can effectively improve the reaction efficiency.

[0022] 2. The graphite phase carbon nitride of the present invention is a polymer organic semiconductor with unique two-dimensional structural characteristics. It relies on strong covalent CN bonds in the plane and relies on van der Waals forces between the layers. It is an easy-to-prepare, non-toxic semiconductor material. The optical band gap of graphite phase carbon nitride is 2.7eV. Due to its good thermal stability and chemical stability, large specific surface area and suitable energy band position, it is widely used in environmental and energy fields such as water decomposition and pollutant degradation. NiFe2O4 is a spinel ferrite magnetic material with good photocatalytic performance. After the degradation is completed, its magnetism can be used to efficiently recover the catalyst, and it has good development prospects in the field of photocatalysis.

[0023] 3. The bismuth oxychloride in the present invention has the characteristics of high photocatalytic activity, high chemical stability and easy band gap adjustment, and is considered to be one of the ideal photocatalysts. As the most widely studied bismuth-based photocatalyst, it is cheap, non-toxic, and has strong redox ability under visible light irradiation. The van der Waals forces between chlorine atoms are interwoven in the inner layer structure of the ternary layered oxide, which can provide sufficient capacity to separate photogenerated charge carriers.

[0024] 4. The method for constructing a Z-type heterojunction using the bismuth-based titanium-based heterojunction material prepared by the present invention improves the ability of the composite material to degrade benzene-containing wastewater, and constructs a heterojunction to remove benzene from the wastewater, achieving satisfactory results.

[0025] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not intended to limit the scope of protection of the present invention. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the reactions are carried out according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources. Example

[0027] Example 1 A method for preparing a bismuth-based titanium-based heterojunction material comprises the following steps: (1) 102 g of bismuth oxychloride, 6 g of titanium dioxide, 5 g of graphite carbon nitride and 8 g of NiFe2O4 were reacted at 180°C for 15 h by a hydrothermal self-assembly method to prepare a bismuth-based titanium-based heterojunction; the particle size of the bismuth oxychloride was 180 nm, and the particle size of the bismuth-based titanium-based heterojunction was 500 nm.

[0028] (2) Distributing surfactant molecules on a bismuth-based titanium-based heterojunction, wherein the surfactant molecules are a dichloromethane solution of an organic substance oleylamine (OAM) with a concentration of 1.8 M, and then standing in an air environment for 10 min to wait for the dichloromethane to completely evaporate, and then using a hydrothermal method, wherein the hydrothermal reaction conditions are 170°C for 14 h, the surfactant molecules guide the thermal growth, the thermal growth temperature is 80°C, and the thermal growth time is 120 min, to obtain a bismuth-based titanium-based heterojunction material.

[0029] Example 2 A method for preparing a bismuth-based titanium-based heterojunction material comprises the following steps: (1) 100 g of bismuth oxychloride, 12 g of titanium dioxide, 5 g of graphite carbon nitride and 11 g of NiFe2O4 were reacted at 180°C for 15 h by a hydrothermal self-assembly method to prepare a bismuth-based titanium-based heterojunction; the particle size of the bismuth oxychloride was 180 nm, and the particle size of the bismuth-based titanium-based heterojunction was 500 nm.

[0030] (2) Distributing surfactant molecules on a bismuth-based titanium-based heterojunction, wherein the surfactant molecules are a dichloromethane solution of an organic substance oleylamine (OAM) with a concentration of 1.8 M, and then standing in an air environment for 10 min to wait for the dichloromethane to evaporate completely, and then using a hydrothermal method, wherein the hydrothermal reaction conditions are 180°C for 14 h, the surfactant molecules guide the thermal growth, the thermal growth temperature is 80°C, and the thermal growth time is 120 min, to obtain a bismuth-based titanium-based heterojunction material.

[0031] Example 3 A method for preparing a bismuth-based titanium-based heterojunction material comprises the following steps: (1) 50 g of bismuth oxychloride, 6 g of titanium dioxide, 3 g of graphite carbon nitride and 9 g of NiFe2O4 were reacted at 180°C for 15 h by a hydrothermal self-assembly method to prepare a bismuth-based titanium-based heterojunction; the particle size of the bismuth oxychloride was 150 nm, and the particle size of the bismuth-based titanium-based heterojunction was 400 nm.

[0032] (2) Distributing surfactant molecules on a bismuth-based titanium-based heterojunction, wherein the surfactant molecules are a dichloromethane solution of an organic substance oleylamine (OAM) with a concentration of 1.8 M, and then standing in an air environment for 10 min to wait for the dichloromethane to completely evaporate, and then using a hydrothermal method, wherein the hydrothermal reaction conditions are 170°C for 14 h, the surfactant molecules guide the thermal growth, the thermal growth temperature is 80°C, and the thermal growth time is 120 min, to obtain a bismuth-based titanium-based heterojunction material.

[0033] Example 4 A method for preparing a bismuth-based titanium-based heterojunction material comprises the following steps: (1) 78 g of bismuth oxychloride, 10 g of titanium dioxide, 5 g of graphite carbon nitride and 10 g of NiFe2O4 were reacted at 180°C for 15 h by a hydrothermal self-assembly method to prepare a bismuth-based titanium-based heterojunction; the particle size of the bismuth oxychloride was 180 nm, and the particle size of the bismuth-based titanium-based heterojunction was 500 nm.

[0034] (2) Distributing surfactant molecules on a bismuth-based titanium-based heterojunction, wherein the surfactant molecules are a dichloromethane solution of an organic substance oleylamine (OAM) with a concentration of 1.8 M, and then standing in an air environment for 10 min to wait for the dichloromethane to completely evaporate, and then using a hydrothermal method, wherein the hydrothermal reaction conditions are 170°C for 14 h, the surfactant molecules guide the thermal growth, the thermal growth temperature is 80°C, and the thermal growth time is 120 min, to obtain a bismuth-based titanium-based heterojunction material.

[0035] Application Examples Application Example 1 20 mg of the bismuth-based titanium-based heterojunction material prepared in Example 1 was weighed and added to 50 ml of deionized water containing 20 mg of benzene molecules. The mixed solution of the catalyst and the benzene solution was magnetically stirred for 30 minutes under dark conditions at a magnetic stirring speed of 880 r / min. After reaching adsorption-desorption equilibrium, a photocatalytic reaction was carried out under visible light with a wavelength of 380-780 nm. Samples were taken every 20 minutes, and the photocatalytic reaction was carried out for 100 minutes. Finally, the obtained samples were subjected to infrared analysis to determine the concentration of the benzene solution after photocatalysis.

[0036] Application Example 2 20 mg of the bismuth-based titanium-based heterojunction material prepared in Example 2 was weighed and added to 50 ml of river water containing 20 mg of benzene molecules. The mixed solution of the catalyst and the benzene molecule solution was magnetically stirred for 30 minutes under dark conditions at a magnetic stirring speed of 880 r / min. After reaching adsorption-desorption equilibrium, a photocatalytic reaction was carried out under visible light with a wavelength of 380-780 nm. Samples were taken every 20 minutes, and the photocatalytic reaction lasted for 100 minutes. Finally, the concentration of the benzene molecule solution was tested for the obtained samples, and the degradation rate was 98%.

[0037] Application Example 3 20 mg of the bismuth-based titanium-based heterojunction material prepared in Example 3 was weighed and added to 50 ml of deionized water containing 20 mg of benzene molecules. The mixed solution of the catalyst and the benzene solution was magnetically stirred for 30 minutes under dark conditions at a magnetic stirring speed of 880 r / min. After reaching adsorption-desorption equilibrium, a photocatalytic reaction was carried out under visible light with a wavelength of 380-780 nm. Samples were taken every 20 minutes, and the photocatalytic reaction was carried out for 100 minutes. Finally, the obtained samples were subjected to infrared analysis to determine the concentration of the benzene solution after photocatalysis.

[0038] Application Example 4 20 mg of the bismuth-based titanium-based heterojunction material prepared in Example 4 was weighed and added to 50 ml of tap water containing 20 mg of benzene molecules. The mixed solution of the catalyst and the benzene solution was magnetically stirred for 30 minutes under dark conditions at a magnetic stirring speed of 880 r / min. After reaching adsorption-desorption equilibrium, a photocatalytic reaction was performed under visible light with a wavelength of 380-780 nm. Samples were taken every 20 minutes, and the photocatalytic reaction lasted for 100 minutes. Finally, the obtained samples were subjected to infrared analysis to determine the concentration of the benzene solution after photocatalysis.

[0039] Table 1 Degradation efficiency of application examples 1-4 As can be seen from Table 1, the degradation rate of benzene-containing wastewater in Application Example 2 is relatively high, which illustrates the method of constructing a Z-type heterojunction using the prepared bismuth-titanium-based heterojunction material, improving the ability of its composite material to degrade benzene-containing wastewater, and constructing a heterojunction to remove benzene from wastewater, and obtained satisfactory results.

[0040] The above is only an exemplary embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A bismuth-based titanium-based heterojunction material, characterized in that: It includes a bismuth-titanium-based heterojunction and surfactant molecules. The bismuth-titanium-based heterojunction includes bismuth oxychloride, titanium dioxide, graphite phase carbon nitride and NiFe2O4. The bismuth-titanium-based heterojunction material is obtained by distributing the surfactant molecules on the bismuth-titanium-based heterojunction and guiding the thermal insulation growth.

2. The bismuth-based titanium-based heterojunction material according to claim 1, characterized in that: The bismuth oxychloride, titanium dioxide, graphite carbon nitride and NiFe2O4 are used to synthesize a heterojunction through a hydrothermal self-assembly method.

3. The method for preparing the bismuth-based titanium-based heterojunction material according to claim 1 or 2, characterized in that: The following steps are involved: (1) Bismuth-based titanium heterojunction was prepared by hydrothermal self-assembly of bismuth oxychloride, titanium dioxide, graphite carbon nitride and NiFe2O4; (2) The surfactant molecules are distributed on the bismuth-titanium-based heterojunction, and the bismuth-titanium-based heterojunction material is prepared by a hydrothermal method, in which the surfactant molecules guide the heat preservation growth.

4. The method for preparing the bismuth-based titanium-based heterojunction material according to claim 3, characterized in that: In step (1), the mass ratio of bismuth oxychloride, titanium dioxide, graphite carbon nitride and NiFe2O4 is 20-100:5-12:3-5:8-11.

5. The method for preparing the bismuth-based titanium-based heterojunction material according to claim 3, characterized in that: In step (1), the particle size of bismuth oxychloride is 50 to 300 nm.

6. The method for preparing the bismuth-based titanium-based heterojunction material according to claim 3, characterized in that: In step (1), the particle size of the bismuth-based titanium-based heterojunction is 300 to 600 nm.

7. The method for preparing the bismuth-based titanium-based heterojunction material according to claim 3, characterized in that: In step (2), the hydrothermal reaction is carried out at 170-200° C. for 14-16 h.

8. The method for preparing the bismuth-based titanium-based heterojunction material according to claim 3, characterized in that: In step (2), the surfactant molecule is a fatty amine, the temperature of the thermal insulation growth is 60-80° C., and the thermal insulation growth time is 100-120 min.

9. Use of a bismuth-based titanium-based heterojunction material prepared by the preparation method according to any one of claims 1 to 8 in treating pollutants.

10. Use of a bismuth-based titanium-based heterojunction material prepared by the preparation method according to any one of claims 1 to 8 in degrading benzene-containing wastewater.